Effect of the post treatments for biowaste‐based digestates on water solubility of nutrients and iron‐cyanide (Fe‐CN) complex mobility. (30th June 2019) - Sut‐Lohmann, Magdalena; Knoop, Christine; Raab, Thomas
Abstract: With recent policy developments, an increase in organic waste utilization is expected. However, the use of organic amendments to reduce the mobility of iron‐cyanide (Fe‐CN) complexes and simultaneously promote vegetation growth has not been studied before. Therefore, we evaluated the effect of (a) drying, (b) composting, and (c) pelletizing on the ability of digestates (biowastes from an anaerobic treatment of municipal organic waste) to provide easily available nutrients and stabilize Fe‐CN complexes. Extraction with deionized water resulted in a considerably higher nutrient and carbon elution from air‐dried and oven‐dried digestates (50% dry matter [DM] of total K, 11% DM Mg, 7% DM Ca, and 6% DM C). Mixer‐pelletized digestates stand out among the composted samples (42% of total K, 3% DM C, 5% DM P, 1.5% DM Mg, and 1% DM Ca). The adsorption experiment showed the highest significant tot. CN conc. reduction using noncomposted, air‐dried (100%), and oven‐dried (82%) digestates. Significant correlations have been found for Mg, Ca, and dissolved organic carbon elution and slightly acidic pH as well as CN adsorption. The Fourier transform infrared analysis revealed Fe‐CN complexation on inorganic (K2 Mn[Fe II (CN)6 ] and NH4 Fe[Fe II (CN)6 ]) and organic constituents indicating formation of nitriles. Air‐ and oven‐dried digestates showed the most promising results in terms of nutrients' availability and ability to decrease Fe‐CN complex mobility.